From texts to films: adaptations of Pride and Prejudice, Jane Eyre and Great Gatsby across the 20th and the 21st centuries - Nabi, Papiya (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2016.